The Influence of Company Size, Public Share Ownership, and Profitability on the Completeness of Financial Statement Disclosure - Anggraini Puspita, Vina; Ridho, Muhammad (Accounting Study Program, Faculty of Economics and Business, 2024)
This study aims to examine the influence of company size, public share ownership proportion, and profitability on the completeness of financial statement disclosures in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The population in this study includes all property and real estate companies listed on the IDX within the specified period. Using the purposive sampling technique, a total of 24 companies were selected with data spanning 3 years, resulting in a total sample of 72. Data processing in this study was conducted using Microsoft Excel and SPSS version 26. Based on the data analysis, the following conclusions were drawn: 1) The t-test results indicate that the company size variable does not significantly influence the completeness of financial statement disclosures, as evidenced by a significance value of 0.066 (above 0.05). 2) The public share ownership proportion variable has a positive and significant influence on the completeness of financial statement disclosures, with a significance value of 0.000 (below 0.05). 3) The profitability variable does not significantly influence the completeness of financial statement disclosures, as indicated by a significance value of 0.078 (above 0.05).